Analisis Kemampuan Shooting Tree Point Dalam Permainan Bola Basket Peserta Didik UPT SMAN 6 Bone - Andi Rizal; A.Feryadi Bangsawan; Iskandar (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
This research is a categorical descriptive study regarding the Tree Point shooting ability in the basketball game of SMAN 6 Bone students whose level of ability is still uncertain. This research aims to find out and ascertain how good the level of basic football skills is, namely Tree Point shooting. This research involved a total of 20 students as samples. The instrument used is a tree point shooting ability test from 3 shooting angles, namely: 0 degrees, 90 degrees and 135 degrees. (Dwi (2020). The data analysis method is accumulating and analyzing the scores for each movement phase and tree point shooting point, then analyzing the percentage to determine the tree point shooting ability level category. The results of data analysis show that the level of Tree Point Shooting ability in the ball game Upt SMAN 6 Bone students' basketball is grouped in the